Correction: Normal Levels of Sox9 Expression in the Developing Mouse Testis Depend on the TES/TESCO Enhancer, but This Does Not Act Alone. - Nitzan Gonen; Alexander Quinn; Helen C O'Neill; Peter Koopman; Robin Lovell-Badge (PLoS Genetics)
[This corrects the article DOI: 10.1371/journal.pgen.1006520.].